Modern geometry (Methods and applications). Part III - B A Dubrovin (Springer-Verlag, 1990)
The book contains a concrete exposition of the geometrical and topological methods of the theory of manifolds with their application in mathematics and physics. It also concentrates on homology theory. It contains introduction to the contemporary methods for the calculation of homotopy groups and the classification of manifolds